Main Life Concerns of Elderly in Urban Slums of Surat City, South Gujarat, India - Jain , Naresh; Pawar , AB; Bansal , RK (National Journal of Community Medicine, 2012)
Background: The United Nations principles address the independence, participation, care, self-fulfillment, and dignity of older persons as an ensured priority. Methodology: The study was conducted among elderly people (60 years and above) to know their main life concerns. The questions, validated before preparing questionnaire, were simple and largely close ended. Results: Most people move into old age after a lifetime of poverty, poor nutrition, and healthcare, and years of hard physical labor. Loneliness was the most important life concern of the respondents in this study. Some studies have revealed this earlier. Livelihood; housing; and recreation and entertainment were another life concerns. The respondents were greatly concerned about the demolition threats to their illegal houses. More than 90 per cent of the respondents were concerned of health problems and seeking health care due to poverty and ill health. In public sector health care set up, long queues and difficulty in reaching physician is very cumbersome. Conclusion & Recommendations: Governments need to focus their attention on better penetration of various social security schemes with special emphasis on poor elderly women. It is imperative to endow with the tailor-made recreational facilities like municipal parks, social clubs and drop-in-centers dedicated to elderly. There is a need to generate political will to understand health issues and life concerns of elderly. Special queue for elderly in health care facilities and geriatric clinics manned by the cadre of specialists/ geriatricians is the need of the hour.